PENGARUH UKURAN DIAMETER LUBANG DALAM ARAH MEMANJANG TERHADAP KEKUATAN TEKAN BENDA UJI SILINDER BETON - Helwiyah Zain (Jurnal Teknik Sipil Unaya, 2017)
Design of buildings should pay attention to aspects; Strength, comfort, economics, and aesthetics. One aspect of the aesthetic that is often seen is the rain water pipeline from the roof to the channel on the ground. In order for this pipe is not be seen from the outside, it can be done by aasembling into thecore of the column so that it looks beautiful. To know the effect of hole in the column, need to do research. The aim of this research is to find out the influence of the variation of the size of the longitudinal aperture in the cylindrical specimen against the compressive strength of the concrete. The number of specimen  were 20 pieces, consisting of 15 pieces of specimens given pipe holes and 5 pieces are not given a hole (intact). Variations of hole size, namely: 2.5 cm, 5 cm and 7.5 cm. Each variation of hole size of specimen 5 pieces. Concrete mixture design is done based on ACI method. The specimens used in this research are cylindrical shape specimens with diameter 15 cm and height 30 cm. Testing of concrete compression done at age 28 days. The test of the specimen is carried out by giving the compression load slowly until the specimen failured. The test results obtained the compressive strength of the specimen without hole = 266.48 kg / cm2;  specimen with hole diameter 2.5 cm = 243,08 kg / cm2; specimen with hole diameter 5 cm = 226,22 kg / cm2; and specimen with hole diameter 7.5 cm = 190,13 kg / cm2. The results of this experiments show that the specimen with diameter of  hole 2.5 cm is 91% of the specimen without hole, the specimen with hole diameter 5 cm is 85% of the specimen without hole; and the specimen with hole diameter 7.5 cm is 71% of the specimen without hole. The results of this experimen show that the larger size of the hole in the column the smaller the compressive strength of the concrete compared to the specimen without holes.